2016
DOI: 10.1016/j.bjid.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral drugs saquinavir and ritonavir reduce inhibitory concentration values of itraconazole against Histoplasma capsulatum strains in vitro

Abstract: Recent studies have shown that some drugs that are not routinely used to treat fungal infections have antifungal activity, such as protease inhibitor antiretroviral drugs. This study investigated the in vitro susceptibility of Histoplasma capsulatum var. capsulatum to saquinavir and ritonavir, and its combination with the antifungal itraconazole. The susceptibility assay was performed according to Clinical and Laboratory Standards Institute guidelines. All strains were inhibited by the protease inhibitor antir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Saquinavir or ritonavir synergistically interacts with itraconazole against H . capsulatum [ 53 ]. The inhibition of PbSap represents a promising strategy for the design of new drugs, and a combined therapy using anti-fungal drugs and Sap inhibitors could increase the efficiency of treatment for P .…”
Section: Discussionmentioning
confidence: 99%
“…Saquinavir or ritonavir synergistically interacts with itraconazole against H . capsulatum [ 53 ]. The inhibition of PbSap represents a promising strategy for the design of new drugs, and a combined therapy using anti-fungal drugs and Sap inhibitors could increase the efficiency of treatment for P .…”
Section: Discussionmentioning
confidence: 99%
“…This is not an insignificant question as the yeast and hyphal forms of the dimorphic fungi can have dramatically different susceptibilities. [62][63][64][65][66][67][68][69] For example, early studies with echinocandins showed antifungal effects on the hyphal form of Histoplasma. 67 However, subsequent tests against the yeast form indicated that caspofungin was anywhere from 20-to 1000-fold less effective.…”
Section: Current Antifungal Optionsmentioning
confidence: 99%
“…Interestingly, the anti- Histoplasma activity of the antivirals saquinavir and ritonavir was previously described. 31 …”
Section: Discussionmentioning
confidence: 99%